Integrasi Pendidikan Karakter dalam Kurikulum Berbasis Nilai Afektif dan Psikomotorik : Tantangan dan Peluang - Achmad Rasyid Ridha; Muhammad Alfan Bahij; Azhar Nurachman; Rizka Setiawan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study highlights the integration of character education through affective and psychomotor values within a curriculum. The integration aims to develop not only intellectual skills but also moral and ethical behaviors among students. Key challenges include inadequate teacher training and limited resources for evaluation. On the other hand, government support and technological advances present significant opportunities. The research employed a qualitative descriptive method, focusing on elementary and secondary schools in Indonesia. Findings suggest that collaboration between schools, families, and governments is essential. Furthermore, the use of digital tools can significantly enhance character education. Implications of the study point towards adaptive curricula and enhanced teacher training programs to overcome the challenges of integration.